DOPPLER NON-CONTACT RADAR SENSORS FOR WATER DISCHARGE ESTIMATION: ADVANTAGES AND LIMITATIONS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The use of non-contact doppler flow radars to determine water discharge is a widespread trend in hydrometeorological surveying and monitoring. However, is it reasonable to consider such an instrument as one of the most suitable and perspective for the hydrological observation network? In-situ testing have been carrying out by authors of this article and the analysis performed in scientific papers cannot provide a single-valued positive conclusion on this issue. Obvious advantage of these radars as independent safe mode of operation seems to overweight their obvious weak points. Many "undercurrents" do not allow this method to be recognized as reliable, such as the problem of transition from surface to medium flow velocities, which consists in the data processing apparatus, reliable positioning of the device, blanking distance task and etc. All in all, this article discusses the main advantages and "vulnerabilities" of the use of such an instrument as non-contact doppler radars to determine water discharge from a scientific and practical points of view.